AB0267 ROLE OF FCGAMMA RECEPTORS IIA, IIIA, AND IIIB POLYMORPHISMS IN RHEUMATOID ARTHRITIS SEVERITY. (June 2019) - Mahmoud, Ines; Moalla, Myriam; Sfar, Imen; Saidane, Olfa; Tekaya, Aicha Ben; Tekaya, Rawdha; Bouajina, Elyes; Zegaloui, Hela; Aouini, Saloua; Gorgi, Yousr; Abdelmoula, Leila
Abstract : Background: Fc gamma receptors (FcgR) type IIA IIIA and IIIB play an important role in the recognition of immune complexes (ICs) by binding their Ig-Fc portion. However, it has been demonstrated that FcgR single nucleotide polymorphisms (SNP) leads to low binding affinity alleles (FcgRIIA-131R, IIIA-158V and IIIB NA2). Therefore, we can make an assumption that the presence of these risk alleles could influence the outcome of immune mediated disease such as rheumatoid arthritis (RA). Objectives: The aim of this study was to assess the relationship between functional SNP of FcgR IIA H13R, IIIA V158F and IIIB NA1/NA2 and disease severity scores in RA. Methods: We assessed disease severity in RA patients based on the Health Assessment Questionnaire (HAQ) and Sharp/van der Heijde (mSharp) method. To reduce selection biais, all recruited patients were treated with conventional DMARDs.We considered patients with HAQ score ranged from 2 to 3 as having severe disability. For radiographic evaluation, since there is not validated threshold for joint damage severity, we took mSharp score median value of our population as a reference. Patients underwent FcgRIIA, FcgRIIIA and FcgRIIIB SNP study using PCR-SSP and direct sequencing process. Then, biallelic polymorphisms were examined for association with HAQ and mSharp score. Results: Fifty-eight RA patients were enrolled. The mean duration of the disease was 11.77 years [0.5-24]. Among these patients, 34 (58.62%) had severe disability according to HAQ score. The mSharp median value was 43, 5 [0-232] and 28 (48.28%) patients had a score above this value. Genotypic study showed that FcgR IIIB-NA2 was significantly associated with severe disability (p=0.021) (Table 1 ). Furthermore, FcgRIIIA-158F and IIA-131R carriers were more frequent in patients with severe disability but the association was not statistically significant. Finally, no correlation was found between radiographic evaluation and FcgR SNP study (table 2 ). Conclusion: FcgR low affinity alleles seem to confer susceptibility to severe functional impairment in RA but not to structural damage. However further studies on larger population must be done to corroborate these findings. References: [1] Brun JG, Madland TM, Vedeler CA. Immunoglobulin G Fc-receptor (FcgammaR) IIA, IIIA, and IIIB polymorphisms related to disease severity in rheumatoid arthritis. J Rheumatol. 2002;29:1135–40. [2] Kastbom A, Ahmadi A, Soderkvist P, Skogh T. The 158V polymorphism of Fc gamma receptor type IIIA in early rheumatoid arthritis: increased susceptibility and severity in male patients (the Swedish TIRA project) Rheumatology (Oxford)2005;44:1294–8. [3] Lee YH, Bae SC, Song GG. FCGR2A, FCGR3A, FCGR3B polymorphisms and susceptibility to rheumatoid arthritis: a meta-analysis.Clin Exp Rheumatol. 2015 Sep-Oct; 33 (5):647-54. Disclosure of Interests: None declared